Morse Theory for Filtrations and Efficient Computation of Persistent Homology - Mischaikow, Konstantin; Nanda, Vidit (Discrete & computational geometry, 2013)
We introduce an efficient preprocessing algorithm to reduce the number of cells in a filtered cell complex while preserving its persistent homology groups. The technique is based on an extension of combinatorial Morse theory from complexes to filtrations.